Ropivacaine represses the proliferation, invasion, and migration of glioblastoma via modulating the microRNA-21-5p/KAT8 regulatory NSL complex subunit 2 axis. Issue 3 (1st March 2022) - Deng, Zexiang; Jian, Yanping; Cai, Hongwei
ABSTRACT: Ropivacaine (Rop) is available to suppress the growth of glioblastoma (GBM), while its mechanism has not been completely elaborated. In this study, we explore the latent mechanism of Rop repressing GBM's growth via mediating the microRNA (miR)-21-5p/KAT8 regulatory NSL complex subunit 2 (KANSL2) axis. MiR-21-5p was declined in GBM, while KANSL2 was elevated. Clinical association studies manifested miR-21-5p was distinctly linked to the tumor size and grade of GBM. Rop constrained GBM cell proliferation, invasion, and migration but boosted apoptosis. Elevated miR-21-5p strengthened Rop's action, while augmented KANSL2 weakened Rop's role. Furthermore, the impact of silencing miR-21-5p on GBM was turned around via declining KANSL2 in Rop-treated GBM cells. KANSL2 was the target gene of miR-21-5p. In short, Rop exerted an anti-tumor impact on GBM via mediating the miR-21-5p/KANSL2 axis, which offered novel viewpoints for the later adoption of Rop as GBM drugs. Graphical Abstract: uf0001